2022
DOI: 10.3390/polym14245385
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanical Degradation of Recycled Polylactic Acid Filaments for Three-Dimensional Printing Applications

Abstract: The recycling of filaments used in three-dimensional (3D) printing systems not only mitigates the environmental issues associated with conventional 3D printing approaches but also simultaneously reduces manufacturing costs. This study investigates the effects of successive recycling of polylactic acid (PLA) filaments, which were used in the printing process, on the mechanical properties of recycled filaments and printed objects. The mechanical strengths of the printed PLA and the adhesion strengths between 3D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…A particularity of this unconventional process is the adhesion of the coating using polymer materials. Layer adhesion refers to the cohesive bonds formed between consecutive layers of material during the additive manufacturing process, ensuring the structural integrity and stability of the printed object [25][26][27][28]. with a Grid infill, the Flexure load at Tensile Strength recorded a value of 300 N. Utilizing a Gyroid infill pattern resulted in recorded forces reaching a value of 379 N, whereas the employment of a Triangles infill pattern yielded forces measuring at 232 N. All values are presented in Tables 3 and 4.…”
Section: Analisys Of the Lateral Thigh Pivotal Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A particularity of this unconventional process is the adhesion of the coating using polymer materials. Layer adhesion refers to the cohesive bonds formed between consecutive layers of material during the additive manufacturing process, ensuring the structural integrity and stability of the printed object [25][26][27][28]. with a Grid infill, the Flexure load at Tensile Strength recorded a value of 300 N. Utilizing a Gyroid infill pattern resulted in recorded forces reaching a value of 379 N, whereas the employment of a Triangles infill pattern yielded forces measuring at 232 N. All values are presented in Tables 3 and 4.…”
Section: Analisys Of the Lateral Thigh Pivotal Componentsmentioning
confidence: 99%
“…A particularity of this unconventional process is the adhesion of the coating using polymer materials. Layer adhesion refers to the cohesive bonds formed between consecutive layers of material during the additive manufacturing process, ensuring the structural integrity and stability of the printed object [25][26][27][28]. In the second test, the joint consisted of components obtained through 3D printing utilizing PLA as the material.…”
Section: Analisys Of the Lateral Thigh Pivotal Componentsmentioning
confidence: 99%
“…While nozzles with a small outlet (diameter down to 100 μm) are able to produce fine structures, the force required to extrude molten polymer from a fine nozzle increases dramatically and potentially leads to the buckling/breakage of feedstock filaments. An elevated temperature may reduce the viscosity of polymer melts to ease the extrusion; however, this would be at the expense of more pronounced thermal degradation of the polymer and compromised mechanical properties of the fabricated objects [ 140 ].…”
Section: Additive Manufacturing Of Bg and Bg/polymer Composites And T...mentioning
confidence: 99%
“…A study by Yu et al [69] demonstrated that compounding talc with PLA improved various mechanical properties, including tensile strength, toughness, Young's modulus, flexural strength, and flexural modulus, up to a certain talc content. They also observed an increase in ultimate strain up to a specific talc content.…”
Section: Mechanical Properties 451 Tensile Propertiesmentioning
confidence: 99%